Unduloribates from North America (Acari, Oribatida, Unduloribatidae) - Behan-Pelletier, Valerie M.; Walter, David E. (Zootaxa, 2009)
We propose a new species of oribatid mite, Unduloribates dianae sp. nov., based on material collected from a variety of boreal habitats in the Canadian Provinces Newfoundland, Nova Scotia, Québec, Alberta and British Columbia, and in New York State in the USA. This is the first species in this genus from the Nearctic. Description is based on adults and all immature stages. We present an expanded generic diagnosis and a key to world species of Unduloribates, and argue for the retention of Unduloribatidae as a monogeneric family in Phenopelopoidea.